2003
DOI: 10.1165/rcmb.2003-0014oc
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Presentation by Local Macrophages Promotes Nonallergic Airway Responses in Sensitized Mice

Abstract: Local inflammatory responses involve relocating immune functions generated by previous immunization to confined parts of the body, and hence are presumed to reflect the prevailing systemic immune bias. To verify to what extent local antigen-presenting cells (APCs) may modulate immune inflammation, we analyzed the consequences of antigen presentation by macrophages on Th2-dependent airway inflammation in ovalbumin (OVA)-sensitized mice. In contrast to challenge with free OVA, which triggers airway eosinophilia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…Depletion of alveolar Mw increased the IgE responses [18] and adoptive transfer of alveolar Mw abrogated AHR [19]. Recently, PYNAERT et al [27] showed that spleen Mw, loaded with OVA and intratracheal-administered, suppressed airway eosinophilia, probably, by inducing a Th1-mediated counter regulation in the lung [8,27]. In contrast, in the present study evidence was obtained for an indirect mechanism by which Mw can suppress anti-inflammatory responses in the lung.…”
Section: Discussioncontrasting
confidence: 58%
“…Depletion of alveolar Mw increased the IgE responses [18] and adoptive transfer of alveolar Mw abrogated AHR [19]. Recently, PYNAERT et al [27] showed that spleen Mw, loaded with OVA and intratracheal-administered, suppressed airway eosinophilia, probably, by inducing a Th1-mediated counter regulation in the lung [8,27]. In contrast, in the present study evidence was obtained for an indirect mechanism by which Mw can suppress anti-inflammatory responses in the lung.…”
Section: Discussioncontrasting
confidence: 58%
“…In this study, we analyzed the molecular mechanism by which OprI exerts its adjuvant effect and examined whether transmucosal administration of OprI could alter the immunological and physiological manifestations of asthma using a mouse model of OVAinduced allergic asthma (17). We found that OprI affects the function of APCs by enhancing their ability to trigger naive T cells and confer to them the capacity to induce the development of Th1 cells.…”
Section: Asthma Is An Inflammatory Lung Disease That Is Initiated Andmentioning
confidence: 99%
“…In addition, they play a role in in vivo Th2 cell priming and a critical role in secondary Th2 responses [14, 15, 39, 194, 195, 196, 197, 198, 199, 200]. In contrast to an apparent role for DC in allergic asthma, the function of macrophages remains unclear despite their obvious abundance within the lungs and inflammatory infiltrates [17, 201, 202, 203, 204, 205, 206]. …”
Section: Lessons From Mouse Models About Pathogenesismentioning
confidence: 99%